Case report: Unusual breast cancer metastasis manifesting as a scalp lesion in a patient with invasive lobular carcinoma - Koh, Nam Hee; Oh, Ha Yeun (Frontiers in Oncology, 2024)
Breast cancer is the most prevalent cancer in women globally, often leading to distant metastasis in the lung, liver, or bones. Cutaneous metastasis represents an uncommon pattern in breast cancer, but when observed, it tends to manifest in the thorax and upper abdomen, primarily due to lymph node involvement. Therefore, occurrences of cutaneous metastasis on the scalp and extremities are infrequent. Moreover, invasive lobular carcinoma metastasizing to remote skin is rare among the breast cancer. This report presents a case of cutaneous metastasis of invasive lobular carcinoma to the scalp in a patient treated for breast cancer six years ago, with no signs of local recurrence or metastasis to other organs.